Internationalization of Small and Medium Enterprises in the Halal Food Industry - Ho, Kwok Kheong (2011)
Internationalization topics have been widely discussed in past literature. This research has been created to complement internationalization researches around the world and the aim of it is to find out barriers faced by Malaysian SMEs in particular of those in the Halal food industry and the strategies undertaken to overcome the barriers. The research also has a brief overview on the internationalization theories including those that are in the rapid internationalization category. The overview extends to barriers and motives of internationalization as well as the Halal certification or standards.The research is conducted with a qualititative method with three local food and beverage Halal food producers in Malaysia. Three case studies were conducted with representatives from these companies. It is found that in general these companies faced several barriers when internationalizing with the most critical barrier being halal certification. In terms of strategies undertaken to overcome them, they have implemented strategies like designing a more flexible management and investing in high end technological supports to enhance the production processes.